PENGARUH MASSA CENTRIFUGAL ROLLER, SUDUT KEMIRINGAN PULLEY PRIMARY DAN SUDUT JALUR ROLLER TERHADAP PERFORMA MESIN: MASS INFLUENCE OF CENTRIFUGAL ROLLER, PULLEY PRIMARY TILT ANGLE AND ROLLER LINE ANGLE TO ENGINE PERFORMANCE - Faiz Muhammad Mi'radj (Jurnal Teknik Mesin, 2024)
Motorcycle manufacturers have produced automatic motorbikes that have an automatic transmission system or called Continuously Variable Transmission (CVT). The purpose of this study is to compare the engine performance produced by variations in the mass of the centrifugal roller, the variation in the degree of inclination of the primary pulley and the angle of the roller path on automatic motorcycle vehicles. The object of the research was carried out on a 110 cc 4 stroke automatic motorcycle vehicle. The method of this study uses experimental methods and data analysis. The dependent variable is engine performance. The results of this study show that using a 13gr Centrifugal Roller mass with a Primary Pulley tilt angle of 13o and a 10o Roller track angle produces the best power of 7.83 Hp at 6500 Rpm. engine speed and the best torque is produced on a 12gr Centrifugal Roller mass with a Primary Pulley tilt angle of 13o and track angle 15o with a torque value of 24.30 N.m at engine speed of 6500 Rpm and the best fuel consumption is using a Centrifugal Roller mass of 13gr with a Primary Pulley tilt angle of 13o and a Roller track angle of 10o with a value of 139.84 g/kW.h at engine speed of 6500 Rpm.